Teresa Catarella, El romancero gitano-andaluz de Juan José Niño. Pres. de P. M. Piñero. Fundación Machado, Sevilla, 1993; 149 pp. - González, Aurelio (El Colegio de México, 1995)
Se reseñó el libro: El romancero gitano-andaluz de Juan José Niño.